China's strategies in combating terrorism in Xinjiang. - Yuen, Chun Wah. (2010)
The outbreak of the U.S.-led "war on terrorism" has brought China to a new era in combating terrorism. This paper aims to analyse the patterns and rationale of the China's counter-terrorist strategies in Xinjiang after the 9/11 Attack. Before discussing the strategies, it will introduce the so-called "Three Evil" forces and some background information of Xinjiang and Uygur in Chapter 2. In order to narrow down the focus, it will use the Eastern Turkistan Islamic Movement (ETIM) to as an example to illustrate the problem of terrorism in Xinjiang, and its possible threats towards China in Chapter 3. The paper will touch with the China's strategies incounter-terrorism in Chapter 4.